Pulmonary rehabilitation, physical activity, respiratory failure and palliative respiratory care. Issue 7 (14th March 2019) - Spruit, Martijn A; Rochester, Carolyn L; Pitta, Fabio; Kenn, Klaus; Schols, Annemie M W J; Hart, Nicholas; Wouters, Emiel F M; Nava, Stefano; Dreher, Michael; Janssen, Daisy J A; Johnson, Miriam J; Curtis, Randall J; et al.
Abstract : The CIRO Academy in Horn (the Netherlands) organised a 2-day meeting to present and discuss the studies published in 2017 pertaining to key priority areas of respiratory and critical care medicine. This review summarises studies focussing on pulmonary rehabilitation and exercise training, physical activity, chronic respiratory failure and palliative respiratory care published in 2017.